N/S-doped carbon electrode derived from paper waste as a sustainable electric double-layer capacitor - Rahmawati, Fitria; Aini, Nur; Ridwan, Qanita; Paramartha, I Gusti Ayu Filia; Putri, Denis Octareta Amelia; Saputri, Dini Deviana; Nugrahaningtyas, Khoirina Dwi; Heraldy, Eddy; Hidayat, Yuniawan; Nurcahyo, I. F.; Anggraningrum, Ivandini Tribidasari (Center of Biomass & Renewable Energy (CBIORE), 2025)
This research aims to produce N/S-doped Carbon Electrode derived from paper waste (NSCEp) for Electric Double-Layer Capacitor (EDLC). The paper waste holds potential as raw material for carbon production because of its high cellulose content, abundance of availability, and low price. To enhance the electrical performance of the carbon, an activation step was conducted, followed by double doping with nitrogen and sulfur using thiourea. The NSCEp result was analysed to examine its specific diffraction peaks, crystallinity, morphology, and elemental contents. The NSCEp powder was then mixed with dispersant to produce a homogeneous slurry for the electrode film. The EDLC was assembled in a sandwich-like structure, with sodium hydroxide (NaOH) solution impregnated in a separator between the carbon film electrodes. The EDLC assembly was conducted under an argon atmosphere in a CR2032 coin cell. The results found that the NSCEp provides a high electrical conductivity of 1.21 x 102 S/cm. The prepared EDLC achieved the specific capacitance value of 39.555 F/g as determined by cyclic voltammetry (CV) analysis. Furthermore, the EDLC demonstrates high initial charge-discharge capacities of 300.56 mAh/g and 248.88 mAh/g, respectively, at a current of 0.015 A/g. The capacity remains stable for up to 300 charge-discharge cycles.